Long‐term climate forcings to assess vulnerability in North Africa dry argan woodlands. Issue 2 (15th September 2014) - Alba‐Sánchez, Francisca; López‐Sáez, José Antonio; Nieto‐Lugilde, Diego; Svenning, Jens‐Christian; Rocchini, Duccio
Abstract Questions North African dry woodlands constitute mediterranean climatic ecotone ecosystems of vital importance for human livelihoods and local biodiversity. To improve the basis for managing these key ecosystems, we selected a Tertiary relict woodland (Argania spinosa) in order to clarify the sensitivity to long‐term climate change (the present, the past glacial‐interglacial cycle and under future scenarios). We also discuss the impact of long‐term human land use for the distribution of dry woodlands in North Africa. Location North Africa. Methods To assess whether the argan woodland is in equilibrium with current climate, we used species distribution modelling (SDM) to estimate its potential range. Then, SDM was used to estimate its potential distribution during the Last Glacial Maximum (LGM; 21, 000 BP) and the Middle Holocene (Mid‐Holocene; 6, 000 BP). Model predictions for past scenarios were compared with Quaternary palaeorecords to evaluate their accuracy. Finally, we forecasted changes in the potential range to year 2080 to assess its likely future range dynamics. Results At the LGM, suitable areas occurred at more southern latitudes, where the Sahara Desert currently lies, while suitable areas in the Mid‐Holocene shifted northwards, occupying areas similar to those of today. The estimated past distributions are consistent with palaeorecords, providing evidence for the important role of Quaternary climate changes in driving dry woodland range dynamics. The current range‐filling constitutes 44% of the potential distribution, probably primarily reflecting anthropic land‐use effects. Future climate change is forecast not to cause latitudinal/altitudinal range shifts, but rather an overall range contraction. Conclusions The models reflect the high sensitivity of the dry woodland ecosystem to past climate changes, in agreement with palaeorecords. The estimated climatic sensitivity also predicts severe range contraction during future climate change. Consequently, management strategies for dry woodlands should be developed to facilitate their in situ survival, particularly by reducing the currently intensive human pressure.